Fluid Flow In 2-D Single Phase Petroleum Reservoir - Thamir Abdul Hafedh (College of Education for Pure Sciences, 2007)
Abstract The purpose of this paper is to test the Darcy's equation and to investigate, by simulations how it's suitable for use in single-phase oil reservoir, and to be used later in history matching procedure. The model used is a flow in a saturated reservoir and this model similar to steady state two-dimensional (2-D) saturated porous media. Reservoir engineering is based on the understanding of fluid flow in porous media. our aim is to produce a reliable code in Matlab which is relevant for the reservoir process (as simulator), and to be used instead of traditional simulator, Black Oil Applied Simulator Tools (BOAST) which was written in fortran, and widely used in almost works concern reservoir simulation.